2017
DOI: 10.1097/md.0000000000006623
|View full text |Cite
|
Sign up to set email alerts
|

Footwear used by older people and a history of hyperkeratotic lesions on the foot

Abstract: Inadequate footwear, painful and hyperkeratotic lesions (HL) are an extremely common problems amongst older people. Such problems increase the risk of falls, hamper mobility, reduction of quality of life, dignity, and ability to remain independent. The etiology of painful and feet conditions is poorly understood.To discover footwear preferences of older people, pain tolerance may favor presence of HL for the use of inadequate footwear in old age.A sample of 100 participants with a mean age of 74.90 ± 7.01 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In addition, our study showed that age and the HV deformity degree were shown as predictors for kinesiophobia symptoms and pain intensity. These findings were in accordance with prior studies reporting that psychological disorders were linked to musculoskeletal conditions, increasing this association with greater age distribution [8][9][10][11][12][13]. In addition, greater instability was shown in older adults under musculoskeletal disorders [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our study showed that age and the HV deformity degree were shown as predictors for kinesiophobia symptoms and pain intensity. These findings were in accordance with prior studies reporting that psychological disorders were linked to musculoskeletal conditions, increasing this association with greater age distribution [8][9][10][11][12][13]. In addition, greater instability was shown in older adults under musculoskeletal disorders [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…Several psychological disorders, such as depression or sociability and vigor linked to general health-related quality of life alterations, have been associated with musculoskeletal conditions, which may increase with greater age ranges [8][9][10][11][12][13]. In addition, musculoskeletal disorders of the lower limbs may alter body stability, showing a greater instability in older adults [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relationship between FHSQ values showed similar findings with the high, normal or low arch of the participants. Despite there were not statistically significant differences between foot arch height, in the first section present lower scores in the footwear and foot health domains suggesting that adults could experience more foot problems in terms of can putting shoes and believe that their feet are in a poor state of health, without differences as regards MLA [ 33 , 34 , 35 , 36 ], highlighting the importance of regular foot checks in this population.…”
Section: Discussionmentioning
confidence: 75%
“…Using a shoe that does not conform to normal function of an individual and the environment will create alterations in movement patterns seen in gait as highlighted. Additional to the gait changes that have been shown to occur, the clinical effects of illfitting footwear can lead to skin lesions (blisters, hyperkeratotic lesions, rubbing soreness and ulceration) [19,20] It is suggested that in turn these changes can lead on to pathology and pain [21,22]. This indirect association linking the development of a lower limb pathology to choosing to wear illfitting footwear is not based on strong evidence.…”
Section: Ill-fitting Footwearmentioning
confidence: 99%